A systematic review of the major risk factors for type two diabetes among Aboriginal Australians - Utpal K. Mondal; Kedir Y. Ahmed; Subash Thapa; Bernd Kalinna; Sok Cheon Pak; Anayochukwu E. Anyasodor; Shakeel Mahmood; Muhammad J. A. Shiddiky; Allen G. Ross (BMC Public Health)
Abstract Background To investigate the sociodemographic, anthropometric, biochemical, lifestyle and cardiometabolic risk factors associated with type 2 diabetes (T2D) among First Nations Australians. Methods A systematic review of prospective cohorts and cross-sectional studies was conducted. Electronic data sources (MEDLINE/PubMed, Embase, CINHAL, and PsycINFO) were searched for peer-reviewed articles until August 2023. We reviewed observational and interventional studies on T2D that reported sociodemographic, anthropometric, lifestyle, and biochemical risk factors for Australian First Nations people. Narrative synthesis was applied without meta-analysis. We highlighted the major risk factors for T2D by reporting the most significant findings from individual studies in the results. The review followed PRISMA guidelines. Results The review included 20 eligible studies: 12 cross-sectional studies and 8 prospective cohort studies. The findings from these studies showed that First Nations people who resided in very remote areas (Modified Monash Category 7; MM7) (OR = 1.61; 95% CI: 1.03, 2.52), living adjacent to food store stocking “Western” food items (OR = 2.92; 95% CI: 1.51, 5.63), rented their home (OR = 2.07; 95% CI: 1.30, 3.30) and part-time employment (OR = 2.47; 95% CI: 1.54, 3.95) were associated with a statistically higher risk of developing T2D. First Nations people who had obesity class 1 (BMI > 30 kg/m2), central obesity (WC > 88 cm in women; >102 cm in men), and higher waist-to-hip ratio (WHR) (≥ 1.0 in men and 0.85 in women) were more likely to have T2D. First Nations people with elevated triglycerides (≥ 1.7 mmol/L) (OR = 4.9; 95% CI: 2.7, 8.8), one standard deviation (SD) increase in C-reactive protein (CRP) value (AHR = 1.23; 95% CI: 1.05, 1.45) and lower levels of vitamin D (< 53 nmol/L) (AOR = 2.15; 95% CI: 1.10, 2.18) were significantly associated with a higher risk of T2D. However, no significant association was found with either daily smoking or daily alcohol. Conclusion To address the First Nations Health Gap attributed to T2D in Australia, interventions should prioritise remote areas, socioeconomic disadvantage, central obesity, elevated triglycerides, and vitamin D deficiency. This was the first comprehensive systematic review examining sociodemographic, anthropometric, biochemical, lifestyle, and cardiometabolic risk factors associated with T2D among First Nations Australians.